2022
DOI: 10.3389/fmars.2021.789687
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Transport Pathways Adjacent to the East Australian Current Reveal Sources of Productivity for Coastal Reefs

Abstract: The region where the East Australian Current (EAC) separates from the coast is dynamic and the shelf circulation is impacted by the interplay of the western boundary current and its eddy field with the coastal ocean. This interaction can drive upwelling, retention or export. Hence understanding the connection between offshore waters and the inner shelf is needed as it influences the productivity potential of valuable coastal rocky reefs. Near urban centres, artificial reefs enhance fishing opportunities in coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…These three scenarios closely resemble the three modes identified by Ribbat et al (2020b) in a 2-year simulation and defined by Roughan et al (2022) to explore shelf transport pathways. However, as the modes presented here are identified from a multi-decadal (25-year) observation and simulation, we consider them to be more robust because EOF analysis can capture more time-scale variability in a longer time series.…”
Section: Mode 3 (Figuresmentioning
confidence: 61%
See 4 more Smart Citations
“…These three scenarios closely resemble the three modes identified by Ribbat et al (2020b) in a 2-year simulation and defined by Roughan et al (2022) to explore shelf transport pathways. However, as the modes presented here are identified from a multi-decadal (25-year) observation and simulation, we consider them to be more robust because EOF analysis can capture more time-scale variability in a longer time series.…”
Section: Mode 3 (Figuresmentioning
confidence: 61%
“…Previous work in the HSM region by Ribbat et al (2020b) and Roughan et al (2022) showed that there are 3 dominant oceanographic scenarios associated with the separation of the EAC and its eddy field. We use EOF analysis to extract the dominant modes that represent these EAC scenarios from our multi-decadal EAC-ROMS model run, which has been interpolated onto the HSM model grid.…”
Section: Eac Scenariosmentioning
confidence: 99%
See 3 more Smart Citations